2016
DOI: 10.1002/jsfa.7810
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, composition, and functional properties of dried alfalfa (Medicago sativa L.) leaf protein

Abstract: It is technically feasible to extract protein with desirable emulsifying and heat stability properties from dried alfalfa leaves; however, the dried form may not be a practical starting material for protein production, given the difficulty of achieving high yields and high-purity protein product. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 27 publications
5
69
0
Order By: Relevance
“…For instance, Martin et al (Martin et al, ) obtained an almost 100% pure and a highly soluble RuBisCo isolate by combining anion‐exchange and size‐exclusion chromatography. pH precipitation (alkali solubilization and acid‐induced precipitation) is a common practice for extracting plant proteins, although the protein recovery was reported to be lower than 50% for alfalfa leaves and solubility of the acid‐precipitated proteins was considerably compromised (Hojilla‐Evangelista et al, ). However, plant leaf proteins extracted in an alkali environment or acid‐extracted proteins that were redissolved at neutral pH before analysis showed excellent solubility in water (Lamsal et al, ; Zhong et al, ).…”
Section: Extraction Of Rubisco and Factors That Affect Yieldmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, Martin et al (Martin et al, ) obtained an almost 100% pure and a highly soluble RuBisCo isolate by combining anion‐exchange and size‐exclusion chromatography. pH precipitation (alkali solubilization and acid‐induced precipitation) is a common practice for extracting plant proteins, although the protein recovery was reported to be lower than 50% for alfalfa leaves and solubility of the acid‐precipitated proteins was considerably compromised (Hojilla‐Evangelista et al, ). However, plant leaf proteins extracted in an alkali environment or acid‐extracted proteins that were redissolved at neutral pH before analysis showed excellent solubility in water (Lamsal et al, ; Zhong et al, ).…”
Section: Extraction Of Rubisco and Factors That Affect Yieldmentioning
confidence: 99%
“…Additionally, proteins concentrated by ultrafiltration, which were at pH 7.0 before analysis, followed the same trend as the resolubilized proteins and showed a peak of solubility of 90/100 g at pH 9.0. Hojilla‐Evangelista et al () reported a limited solubility for dried alfalfa leaf protein concentrate in the pH range 2.0–10.0, with the lowest solubility observed at pH 4.0 (2/100 g) and the highest solubility at pH 5.5–10.0 (50/100 g). In this study, proteins were extracted by alkali solubilization and acid‐induced precipitation, and the observed results are, therefore, in line with the behavior observed by Lamsal et al () for acid‐extracted proteins.…”
Section: Solubilitymentioning
confidence: 99%
See 2 more Smart Citations
“…neutral pH, low temperature). Protein extraction from dried alfalfa leaves leads to lower yields and less purity than from fresh leaves (Hojilla-Evangelista et al, 2016). Reaching higher yields would require harsh conditions such as using highly alkaline pH (pH14), as described for dried tea leaves (Zhang et al, 2014).…”
Section: B: Stabilising By Freezingmentioning
confidence: 99%